Creating and Teaching an Online Business Case Study Using Twine - Kervyn, Nicolas; Gómez Zúñiga, Rosa; Vangrunderbeeck, Pascal; Castillo Villar, Fernando; Cavazos Arroyo, Judith (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2020)
In this practice report, we present how, in the face of Covid-19, we have transformed a traditional case study into an interactive online case study. This was done during a six-week course from mid-March to May, which had to be reinvented at the last minute as a fully online course. We present the advantages and limitations of this transition and the areas for improvement for the future.